POSITIVE ROLE OF "INTERGENERIC MICROBIAL CO-AGGREGATES", COMPRISING OF PSEUDOMONAS AND PAENIBACILLUS CELLS, ON THE ENHANCEMENT OF INDUCED SYSTEMIC RESISTANCE (ISR) IN MAIZE – HELMINTHOSPORIUM TURCICUM PATHOSYSTEM UNDER SEMIARID CONDITION - S. ESATH NATHEER; C. SEKAR; P. AMUTHARAJ (International Journal of Pharma and Bio Sciences, 2013)
The application effect of different formulations of Pseudomonas fluorescens and Paenibacillus polymyxa cells viz., single strain inoculation, co-inoculation and biofloc application together with challenge inoculation of Helminthosporium turcicum on the enhancement of growth and yield parameters in maize with special emphasis to Induced systemic resistance (ISR) mediated biocontrol against leaf blight disease was studied under pot culture condition with maize cv. Co 1. The application of P. fluorescens and P. polymyxa cells, as biofloc, augmented the growth and yield parameters viz., plant height, root and shoot dry weight, phosphorous, carbohydrate, chlorophyll and IAA content, grain, stalk and cob yield of maize cv. Co 1 and altered the biochemical and physiological parameters of maize plant to a maximum level followed by co-inoculation and single strain application. Moreover, the application of P. fluorescens and P. polymyxa cells, as biofloc, increased the total phenol content and defense enzymes content of maize, reduced the reducing and non-reducing sugar content to a higher level that eventually lead to the reduction in H. turcicum incidence in maize. The results of the present study clearly revealed the positive role of biofloc formulation of P. fluorescens and P. polymyxa cells on the enhancement of maize productivity and maximization of ISR mediated biocontrol in maize – H. turcicum pathosystem under semiarid condition together with a reduction in 25 per cent ‘P’ fertilizer application.